Os incentivos fiscais da Zona Franca de Manaus e a Reforma Tributária com a instituição da Contribuição sobre bens e serviços e do Imposto sobre bens e serviços - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
This dissertation aims to analyze the Tax Reform and its impacts on the tax incentive policy of the Manaus Free Trade Zone. Upon receiving DL 288/67 by art. 40 of the ADCT, CF/88 maintained the ZFM legal regime with differentiated taxation through its tax incentives, preserving its competitive advantage. Through the deductive method and bibliographical research, based on constitutional, tax, financial and economic law, Brazilian doctrine, periodicals, court decisions and government websites. In the first chapter, the constitutionalization of the development of the Amazon will be verified, with the historical context from rubber to industry, followed by the creation and reception of the ZFM by CF/88, and the sustainable development promoted by the economic model. In the second chapter, there will be an analysis of the extrafiscality of the ZFM's tax incentives, with an approach to the transition from the Liberal State to the Social State, the characterization of the Intervening State, taxation and extrafiscality. Next, the modalities of tax incentives, the legal regime of the ZFM and its tax incentives will be verified, ending the chapter with the context of the tax war and the extra-fiscal nature of the ZFM's tax incentives. In the third and final chapter, the context of Tax Reform and ZFM tax incentives will be focused on, also analyzing the Proposed Amendments to the Constitution and the new taxes to be introduced into the legal system, followed by Federalism. Tax and Tax Reform, ending the chapter with an analysis of the possible impacts of Tax Reform on the ZFM. At the end, there will be conclusions of the work with considerations on the research carried out.
The tax incentives of the Manaus Free Zone and the tax reform with the institution of the contribution on goods and services and the tax on goods and services
Keywords: Incentivos fiscais - Legislação; CIENCIAS SOCIAIS APLICADAS: DIREITO: DIREITO PUBLICO: DIREITO TRIBUTARIO; CIENCIAS SOCIAIS APLICADAS: DIREITO: DIREITO PUBLICO: DIREITO CONSTITUCIONAL; Reforma Tributária; Zona Franca de Manaus; Incentivos Fiscais; Extrafiscalidade